INCREASING TEACHER CAPACITY IN PREPARING LEARNING IMPLEMENTATION PLANS (RPP) FOR THE 2013 CURRICULUM THROUGH GROUP TECHNICAL ACADEMIC SUPERVISION IN TASIKMALAYA CITY ASSISTED SCHOOLS (MTSS ATTARBIYAH AND MTSS BAITUL HIKMAH) IN 2019 - Neneng Sugiartini (Institut Pendidikan Indonesia, 2022)
This school action research was motivated by the fact that at MTsS Attarbiyah Tasikmalaya City, of the 36 teachers, only 10 (27.78%) were able to prepare the RPP for Curriculum 13, the remaining 26 people (72.22%) had not been able to prepare the RPP for Curriculum 2013. At MTsS Baitul Hikmah Tasikmalaya City, of the 26 teachers, only 6 (23.08%) were able to prepare (RPP) for the 2013 Curriculum, the remaining 20 (76.92) people had not been able to prepare the RPP for the 2013 Curriculum. This was caused by various things including : (1) teachers' understanding of the preparation of the 2013 Curriculum (RPP) is still lacking; (2) guidance for teachers in preparing the 2013 Curriculum (RPP) has not been optimal (3) most teachers have never participated in workshops on preparing the 2013 Curriculum (RPP); (4) lack of resources that teachers have regarding preparation techniques (RPP) for the 2013 Curriculum; (5) The RPP that teachers have is generally not the product of the teacher himself. This school action research is limited to the problem